Nacionalni pesniki in kulturni svetniki - Dović, Marijan (Primerjalna književnost, 2011)
This paper compares the process of canonization of two Romantic poets, France Prešeren (1800-1849) and Jónas Hallgrímsson (1807-1845), both of whom have undoubtedly reached the status of a "national poet" in their respective cultures (Slovenian and Icelandic). Despite minor dissimilarities in canonisation, several significant traits point that they can also be understood as "cultural saints".
Keywords: Prešeren, France, 1800-1849; Hallgrímsson, Jónas, 1807-1845; nacionalni pesniki; nacionalni literarni kanon; slovenska poezija; islandska poezija; Romanticism; romantika; primerjalne študije